Autism Spectrum Disorders in forensic psychiatric investigations–patterns of comorbidity and criminality - Hofvander, Björn; Nilsson, Thomas; Ståhlberg, Ola; Claesdotter, Emma; Moberg, Patricia; Ahlbäck, Klara; Hildebrand Karlén, Malin (Frontiers in Psychiatry, 2023)
common type of crime was violent crime. Three person-oriented clinical subgroups were identified;(1) ASD with few other diagnoses; (2) ASD and very high levels of SUDs, plus moderate levels of other externalizing disorders and psychotic psychopathology and (3) ASD and moderate to high levels of personality disorders (other than ASPD) and SUDs.Our results highlight the importance of all parts of the CJS to be prepared to handle offenders with ASD, often with high levels of additional psychiatric problems. Traditional approaches in treatment or other psychosocial interventions for ASD may need to be adapted to at least three general clinical profiles-one with mainly neurodevelopmental problems, one with a spectrum of externalizing problems and one with complex personality related difficulties.